Covid-19 And The Practice Of Digital Diplomacy In Ghana - Aboagye Josephine (University of Cape Coast, 2024)
This dissertation examines the practice of digital diplomacy in Ghana during the COVID-19 pandemic. It analyses how diplomatic activities were conducted, the challenges encountered during the pandemic, and the future of digital diplomacy in Ghana. The study also tests whether COVID-19 magnified the use of technology and digital diplomacy in Ghana. Using the mixed method approach, the study reveals that COVID-19 magnified the use of digital tools in the furtherance of diplomatic activities (which is termed as digital diplomacy) in Ghana. The study also reveals that the future of digital diplomacy in Ghana is promising and positive and a combination of traditional and online diplomacy would enhance the conduct of diplomacy. The study identified that the concept and conduct of digital diplomacy came with challenges which were encountered institutional challenges in the context of how digitalisation is diffused in diplomatic contexts, internet connectivity, privacy, and security issues. The study recommends that stakeholders expand their social media presence by establishing and maintaining active and official social media accounts for the relevant ministries and Ghanaian missions abroad to share information, engage with citizens and promote the country‟s interests and values.
xiii,118p:,ill
Keywords: COVID-19 Digital Diplomacy Public Diplomacy Technology Digitalisation